Penerapan Metode Profile Matching Dalam Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Pada Pt. Hyundai Mobil Indonesia Cabang Kalimalang - Heru Purwanto (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2017)
Development of Information and Technology gives space to the industry and business global advancement which has function as Planning and Decision. Information Technology goes into the more strategic business of provider. Owners of the provider deal with a reality to take necessary decision. High technology without good human sources is useless. Leader choice from some of the best candidate is objectively referable to decide a leader in suitable position. Recommendation is not the only one guaranty to choose employee as a leader. It should have a way and method as leader alternative election that suitable with needs. At this research, Profile matching method is used alternatively to give assessment and evaluation of key performance index of each employee as a leader recruitment. There are three aspect of conducting assessment and evaluation. They are Intelligence Aspect, Attitude Aspect, and Behavioral Aspect. There are some levels of Intelligence Aspect; creativity, intelectual activity and solution, initiative, concentration and anticipation. Attitude Aspect has accuracy, responsiblity, control sense, motivation, planning, and carefulness. Lastly, Behavioral Aspect consists of subservience, sincerity, indpendent and dynamic, influence. There is a rank changing from candidate after calculating with profile matching method whose employee within K5 code has first position at 6,55 compared with manually calcualting at second position.